Mediterranean Diet And Longevity: An Example Of Nutraceuticals? - Vasto, Sonya; Barera, Annalisa; Rizzo, Claudia; Di Carlo, Marta; Caruso, Calogero; Panotopoulos, George (Current Vascular Pharmacology, 2014)
The Mediterranean diet (Mediet) is an eating pattern characterizing a lifestyle and culture that has been reported to contribute to better health and quality of life. The Mediet reflects food patterns typical of Mediterranean regions, where olive oil plays an essential role in the food pyramid. Olive oil is located in the middle and it is considered the principal source of dietary fat because of its high nutritional quality (particularly extra virgin olive oil). Several studies have shown the effect of the Mediet on healthy status by lowering the rates of coronary heart disease, certain cancers, and some other age-related chronic diseases. Although the scientific literature regarding diet and life span is complex and with different opinions, there are studies that demonstrate the beneficial effects of the Mediet on longevity. Therefore, the Mediet may be considered as including several nutraceuticals that favourably influence health. In the present review we discuss two Mediterranean populations from the island of Ikaria (Greece) and the Sicani Mounts (Sicily, Italy) whose longevity is attributed to a close adherence to the Mediet.
Keywords: mediterranean diet